Medicolegal Approach to a Case with Erectile Dysfunction after a Traffic Accident - Kaya, Ahsen; Çelik, Cemil; Güler, Hülya; Şenol, Ender (The Bulletin of Legal Medicine, 2019)
Erectile dysfunction is the inability to maintain or to obtain adequate erection for sexual intercourse. In this case report; it was aimed to evaluate erectile dysfunction which developed after a traffic accident due to multi-trauma and to contribute to the guideline for the evaluation of the crimes in forensic medicine.Medical records included pelvic fractures, bladder and urethra ruptures as well as other injuries. Urology consultation was requested after the application of the case to our department. As a result of this, regarding the current findings, it was found that the case was not enough to perform erection in terms of organic aspects.It was concluded that the trauma led to the permanent loss of one of the organs in terms of urology.The inclusion of the erectile dysfunction in the relevant guidelines under the heading of sexual dysfunctions is thought to be helpful in the process of forensic report-making.
Keywords: Forensic medicine; Erectile dysfunction; Pelvic injury; Traffic accident